Solar PV where the sun doesn't shine: Estimating the economic impacts of support schemes for residential PV with detailed net demand profiling - Sarah La Monaca; Lisa Ryan (University College Dublin, UCD School of Economics, 2016)
Countries with low irradiation and solar PV adoption rates are increasingly considering policy support for solar PV, though consumer electricity demand and solar generation profiles are often mismatched. This paper presents a methodology for policy makers in countries with such conditions to examine more precisely the financial performance of residential solar PV from the consumer perspective as part of an ex-ante policy assessment. We model a range of prospective policy scenarios and compare policy mechanisms that compensate homeowners for generation, those that reduce their upfront costs, and those that assist with financing, using Ireland as a case study. The results confirm the intuitive notion that more generous financial remuneration schemes provide quicker payback, however, we observe that upfront grants do little to accelerate payback timeframes. We also show the importance of retail tariff structure in consumer payback for a solar PV system, with one-part tariffs generating shorter paybacks than two-part tariff structures, although the latter is more likely to secure revenue for electricity infrastructure investment. Drawing from this analysis, the paper proposes some options for the design of policy supports and tariff structures to deliver a sustainable residential renewable electricity system.
Keywords: 330